Interventions to decrease the incidence of dispensing errors in hospital pharmacy: a systematic review and meta‐analysis. (8th February 2021) - Poole, Susan G.; Kwong, Elaine; Mok, Belinda; Mulqueeny, Bianca; Yi, Milan; Percival, Mia A.; Marsom, Erica N.; Duncan, Caylen; Graudins, Linda V.
Abstract: Background: Dispensing errors have the potential to cause significant patient harm. Strategies shown to improve the safety of medication dispensing have been widely published, however, there is an absence of literature comprehensively assessing the outcomes of these strategies. Aim: To evaluate the effectiveness of interventions designed to decrease the rate of dispensing errors in hospital pharmacy dispensaries. Methods: A systematic review and meta‐analysis of the peer reviewed literature were conducted. Medline, Embase, CENTRAL and CINAHL were searched to identify comparative studies that evaluated interventions designed to reduce the rate of dispensing errors in hospital pharmacy dispensaries. Data were extracted from eligible studies using a standardised data collection tool. Quality assessment was conducted using the Scottish Intercollegiate Guidelines Network Checklist‐3. Meta‐analysis was performed using a random effects model and presented as risk ratios (RR), with corresponding 95% confidence intervals (CI). Results: Eleven studies were eligible for inclusion. Interventions included implementation of dispensing technologies, accredited technicians performing prescription verification, and addressing look‐alike medications. Five studies detected dispensing errors during final verification (prevented or near‐miss dispensing errors); five studies identified unprevented dispensing errors; one study evaluated both. There was a statistically significant reduction in the pooled rate of dispensing errors from 0.080% in the control group to 0.043% in the intervention group (rate difference 0.037%, 95% CI 0.033–0.042%). Meta‐analysis demonstrated a 34% reduction in the risk of prevented dispensing errors (RR 0.66, 95% CI 0.46–0.93) and 68% reduction in the risk of unprevented dispensing errors (RR 0.32, 95% CI 0.24–0.43). Conclusion: This is the first systematic review and meta‐analysis of the impact of dispensing errors interventions. The results indicate that the implementation of the most effective interventions, such as appropriately trained staff and using technology, results in reductions in dispensing error rates.